Law Enforcement Against Fraud in Banking Committed by the Board of Directors - Tampongangoy, Grace Henni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Fraud undermines public trust in the national banking system and causes financial losses to customers. Despite regulations like Law No. 10 of 1998 on Banking and Financial Services Authority (OJK) provisions, fraud enforcement in Indonesia remains suboptimal due to case complexity, weak oversight, and enforcement challenges. This study explores legal enforcement mechanisms for banking fraud by directors and contributing factors. Using a normative approach, the research analyzes laws, principles, and case studies. Data sources include the Banking Law, Limited Liability Company Law, OJK regulations, academic literature, and reports on fraud cases. Qualitative analysis links regulations to enforcement practices and identifies barriers. Findings show Indonesia's legal framework is comprehensive but inadequately implemented. Weaknesses include limited monitoring of directors abusing authority and difficulties in proving fraud involving complex data manipulation. Key obstacles include weak internal controls, minimal inter-agency coordination, and ineffective application of Good Corporate Governance (GCG) principles at the director level due to a lack of transparency and accountability. To address these gaps, the study recommends strengthening synergies between supervisory institutions and law enforcement, improving internal audits through independent reviews, and specialized training for handling financial cases. Instilling GCG principles among directors is crucial to prevent fraud. This study highlights the need for improved regulation and effective enforcement to enhance banking sector integrity.